2017
DOI: 10.18869/nirp.ijpcp.22.4.340
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of the Relation Between Social Anxiety, Cognitive and Behavioral Aspect of It and Sex and Gender-Rolein Adolescence

Abstract: Objectives Social anxiety is one of the most common disorders of adolescence. Among the factors affecting the disorder to determine the sex (female or male) reported conflicting results, while the relation between gender role consistent with some anxiety disorders. The aim of this study was to compare social anxiety and its cognitive (AFNE) and behavioral (TISC) aspects based on different sex and gender roles (femininity, masculinity, androgyny and indistinct). Methods Students (N=277) aged 12 to 13 years were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
0
1
Order By: Relevance
“…Aliakbari et al (2017) emphasized that the gender role was effective in social phobia. In this study, the mean score of social phobia in women was higher than that of men ( 27 ). However, one study demonstrated no significant relationship between gender and social phobia ( 28 ).…”
Section: Discussioncontrasting
confidence: 46%
“…Aliakbari et al (2017) emphasized that the gender role was effective in social phobia. In this study, the mean score of social phobia in women was higher than that of men ( 27 ). However, one study demonstrated no significant relationship between gender and social phobia ( 28 ).…”
Section: Discussioncontrasting
confidence: 46%